THE ANALYSIS OF FINANCE AND INVESTMENT IN AUTOMOTIVE INDUSTRY OF CHINA - Yajid, Mohd Shukri Ab (International Journal of Psychosocial Rehabilitation, 2020)
---This study is about the auto industry of the china. In this study many analysis have been conducted for the purpose of checking industry performance and found that industry is doing well and generated enough profits and contributed heavily in the GDP of the country. In addition, the entry barrier of automotive industry is very high and the exit barrier of automotive industry is relative lower in China; this characteristic means the investors could have stable high return on their investments of automotive industry in China.